Exploring viscosity, polarity and temperature sensitivity of BODIPY-based molecular rotors - Kuimova,MK; Vysniauskas; Lopez,Duarte; Duchemin; Vu; Wu; Budynina; Volkova; Peña,Cabrera; Ramírez-Ornelas (Physical Chemistry Chemical Physics, 2017)
Microviscosity is a key parameter controlling the rate of diffusion and reactions on the microscale. One of the most convenient tools for measuring microviscosity is by fluorescent viscosity sensors termed ‘molecular rotors’. BODIPY-based molecular rotors in particular proved extremely useful in combination with fluorescence lifetime imaging microscopy, for providing quantitative viscosity maps of living cells as well as measuring dynamic changes in viscosity over time. In this work, we investigate several new BODIPY-based molecular rotors with the aim of improving on the current viscosity sensing capabilities and understanding how the structure of the fluorophore is related to its function. We demonstrate that due to subtle structural changes, BODIPY-based molecular rotors may become sensitive to temperature and polarity of their environment, as well as to viscosity, and provide a photophysical model explaining the nature of this sensitivity. Our data suggests that a thorough understanding of the photophysics of any new molecular rotor, in environments of different viscosity, temperature and polarity, is a must before moving on to applications in viscosity sensing.